On the Gold‐Catalyzed Intramolecular 7‐exo‐trig Hydroamination of Allenes. Issue 7 (30th April 2013) - Pflästerer, Daniel; Dolbundalchok, Praphasiri; Rafique, Shahid; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract Aniline derivatives with allene side tethers were tested as substrates for a gold‐catalyzed 7‐exo‐trig hydroamination reaction. The nucleophilicity of the aniline derivatives plays an important role for the outcome of the reaction. While electron‐deficient protecting groups at the nitrogen led to competing pathways like hydroarylation or an allene to diene isomerization, clean formation of the desired benzoxazepines was obtained with unprotected aniline derivatives.